2022
DOI: 10.1038/s41467-022-32475-x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-tissue analysis of blood and brain epigenome-wide association studies in Alzheimer’s disease

Abstract: To better understand DNA methylation in Alzheimer’s disease (AD) from both mechanistic and biomarker perspectives, we performed an epigenome-wide meta-analysis of blood DNA methylation in two large independent blood-based studies in AD, the ADNI and AIBL studies, and identified 5 CpGs, mapped to the SPIDR, CDH6 genes, and intergenic regions, that are significantly associated with AD diagnosis. A cross-tissue analysis that combined these blood DNA methylation datasets with four brain methylation datasets priori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 112 publications
6
38
0
Order By: Relevance
“…Nevertheless, the genes identified in our trans-ancestral analyses are biologically plausible. CDH6 has been identified as related to AD in both an epigenome-wide analysis 95 and in an agnostic plasma proteomic analysis. 96 It plays a role in both hippocampal synaptic development and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the genes identified in our trans-ancestral analyses are biologically plausible. CDH6 has been identified as related to AD in both an epigenome-wide analysis 95 and in an agnostic plasma proteomic analysis. 96 It plays a role in both hippocampal synaptic development and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these previous results, our comparison of the significant blood DNAm from this study with significant brain DNAm associated with AD pathology in two large recent meta-analyses of postmortem brain tissues [ 9 , 110 ] shows only a few overlapping DNAm (3 CpGs and 8 DMRs), mapped to PRSSL1 , LINGO3 , SPRED2 , HOXA2 , NR2F1 , CPT1B , HOXA5 , ZFPM1 genes, and intergenic regions, were significant with both blood DNAm-to-CSF Aβ 42 /pTau 181 association and brain DNAm-to-brain Aβ/tau association (Supplementary Tables 4 – 9 ). Also, there is not any overlap between significant blood DNAm associated with the CSF AD biomarkers and significant blood DNAm associated with clinical AD from our previous meta-analyses of two large clinical AD datasets [ 17 , 111 ]. This is not surprising, given the disconnection between brain pathology and clinical diagnosis in AD; it has been observed that a substantial proportion of cognitively normal subjects also have AD pathology in the brain [ 20 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, given brain and blood cells originate from different developmental cell lineages, previous studies also suggested that DNA methylation profiles are, by and large, distinct between brain and blood [ 7 , 17 , 109 ]. Consistent with these previous results, our comparison of the significant blood DNAm from this study with significant brain DNAm associated with AD pathology in two large recent meta-analyses of postmortem brain tissues [ 9 , 110 ] shows only a few overlapping DNAm (3 CpGs and 8 DMRs), mapped to PRSSL1 , LINGO3 , SPRED2 , HOXA2 , NR2F1 , CPT1B , HOXA5 , ZFPM1 genes, and intergenic regions, were significant with both blood DNAm-to-CSF Aβ 42 /pTau 181 association and brain DNAm-to-brain Aβ/tau association (Supplementary Tables 4 – 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the modest number of samples with both DNA methylation and CSF biomarker measurements, we expected our analysis to be underpowered. Therefore, based on our experiences and previous studies in the analysis of EWAS measured in blood 37,42,43 , we also prioritized CpGs with suggestive signi cance at the pre-speci ed signi cance threshold P-value < .…”
Section: In Ation Assessment and Correctionmentioning
confidence: 99%